Isolation and purification of glutathione s-transferases from donax sp / Norfarhan Mohd Assa’Ad - Mohd Assa’Ad, Norfarhan (2011)

(untitled)
Glutathione S-transferases (GSTs) are among the enzymes involved in the phase II detoxification metabolism of wide range exogenous and endogenous compounds in living cells. Bivalves GSTs often proposed as biomarker for marine pollution detection for several reasons; filter feeder, sessile, wide range distribution, and not affected by some biotic factors. In this study, GSTs from remis Donax sp. was purified by using two affinity column; GSTrapTMHP and GSH-agarose (C3). The total recovery of CDNB-active GSTs was 12% and 3% for GSTrapTMHP and GSH-agarose (C3), respectively. SDS-PAGE of GSTrapTMHP purified extract revealed two subunits with apparent molecular masses (MW) of 29 and 26 kDa while GSH-agarose (C3) showed three subunits corresponding to 29, 28, and 26 kDa. Two-dimensional electrophoresis (2-DE) of GSTs purified from GSH-agarose (C3) discovered nine similar spots to GSTs purified using GSTrapTMHP but with additional six distinct spots. Analysis by isoelectric focusing (IEF) illustrated most GSTs purified from both column resolved at pI in between 4.5 to 6.9. Apart from this cluster, there were also GSTs appearing each at pI 4.2 and 8.3. Purified GSTs from both columns exhibited activity towards 1-chloro-2,4-dinitrobenzene (CDNB), 1,2-dichloro-4-nitrobenzene (DCNB), sulfobromophthalein (BSP) and ethacrynic acid (EA). GSH-agarose (C3) showed less specific activity in all substrates compared to GSTrapTMHP, except for EA which count about 10- fold. However, GSTs eluted from both columns did not show any activity with p-nitrobenzylchloride (NBC), trans-4-phenyl-3-butene-2-one (PBO), and nitrocinnamaldehyde (NCA). However, mass spectrometry analysis did not show any match with the available database. Therefore based on the current data, GSTs obtained in this study were summarized belong to pi- and mu-class.